Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
quoc duc nguyen

a) -x^4+2x^3-2x^2+2x-3=0

b) x^3-6x^2+11x-12=0

Không Tên
2 tháng 2 2018 lúc 20:09

b)     \(x^3-6x^2+11x-12=0\)

\(\Leftrightarrow\)\(x^3-4x^2-2x^2+8x+3x-12=0\)

\(\Leftrightarrow\)\(x^2\left(x-4\right)-2x\left(x-4\right)+3\left(x-4\right)\)

\(\Leftrightarrow\)\(\left(x-4\right)\left(x^2-2x+3\right)=0\)

Ta có:    \(x^2-2x+3\)

        \(=\left(x-1\right)^2+2>0\)

\(\Rightarrow\)\(x-4=0\)

\(\Leftrightarrow\)\(x=4\)

Vậy...


Các câu hỏi tương tự
Trang Kieu
Xem chi tiết
Đàm Hương Giang
Xem chi tiết
vân nguyễn
Xem chi tiết
Linh Hoàng
Xem chi tiết
Bùi Minh Huy
Xem chi tiết
18. Đào Gia Hân
Xem chi tiết
Sỹ Tiền
Xem chi tiết
Trọng Nghĩa Nguyễn
Xem chi tiết
Thư Phạm
Xem chi tiết